Efeito antibacteriano do preparo biomecânico e de uma pasta à base de hidróxido de cálcio sobre bactérias presentes em canais radiculares de dentes decíduos necrosados após trauma - Sousa, Denise Lins de (2008)
One of the main objectives of endodontic treatment of roots canals with necrotic pulps consists in eliminating the microorganisms spread throughout the ramifications of root canal system. This study, comprised by one manuscript, had the objective to evaluate the antiseptic efficacy of biomechanical preparation and a calcium hydroxide-paste in root canals of human primary teeth with necrotic pulp after trauma and to detect the microorganisms Fusobacterium nucleatum and black-pigmented bacilli in this teeth. According to stringent inclusion criteria, 18 primary teeth with necrotic pulp were selected. Bacterial samples were taken after crown access (S1) and 72h after the removal of dressing with a calcium hydroxide paste (S3), but to 10 teeth were taken a other bacterial sample after chemomechanical preparation with 0.5% NaOCl as an irrigant (S2). Bacteriological samples were collected by introducing 3 sequential sterile absorbent paper points, of a size visually compatible with the root canal diameter. After approximately 1 min, the paper points were removed and placed in a test tube containing reduced transport fluid and were sent for microbiological evaluation. In the S1, the microorganisms were found in 7/18 (94,4%) of the samples, with a colony forming units (CFU’s) media of 5.4 x 105. In the S2, bacteria were cultured in only 1/10 (10%) root canal, with the CFU’s media of 4.3 x 102, and in the S3 bacteria were cultured in 15/18 (83.3%), with the CFU’s media of 1.5 x 105. A statistically significant reduction in bacterial counts was observed between S1 and S2, however no statistically significant difference was observed for comparisons involving S1 and S3, and S2 and S3. The microorganisms Fusobacterium nucleatum and black-pigmented bacilli were detected in 55.5% (10/18) and 11.1% (2/18), respectively, in the S1, no were found in the S2, and in the S3 were found in 16.6% (3/18) and 5.5% (1/18), respectively. In the S1, the gram-negative cocci (15/18) and gram-negative rods (14/18) were the most prevalent groups (83.3% and 77.8%, respectively). In the S2, the gram-positive cocci was the only group of the bacteria observed (1/10), and in the S3, the gram-positive cocci was the group most commonly recovered (66.7%). It was conclude that biomechanical preparation were important in the antisepsis of the root canal because reduced significantly the number of bacteria in the main canal however the calcium hydroxide paste had a antibacterial efficacy limited, no prevent the regrowing bacterial after used as dressing intracanal.